Socialization and Nurturing Entrepreneurship Among Indian Women - Singh, Pooja (Prabandhan: Indian Journal of Management, 2013)
Women entrepreneurs cannot gain momentum if the ground for entrepreneurship remains uneven. Analysis of literature from the psychological and sociological perspective has deduced that childhood socialization is one of the most important determinants of entrepreneurship development. The paper discusses how self help groups can establish a link with women entrepreneurial development. This paper tries to show how access and control of resources for the development of the entrepreneurial mindset right from childhood is of great importance. Access and control of resources by women has been linked to the life cycle theory. The paper wishes to draw attention of the family, society, and the government towards a change in upbringing of the girl child, who later on in life can be helpful in changing the picture of women entrepreneurship in India. The paper shows that if the girl child is allowed to grow independently, then both male and female entrepreneurs can be created in the Indian society.